THE RELATIONSHIP BETWEEN STUDENTS ATTITUDE TO HEALTH EDUCATION AND LEARNING ENVIRONMENT BY LEARNING OUTCOMES OF HEALTH EDUCATION IN THE FIFTH DEGREE ELEMENTARY SCHOOL - Sumantri, Mohamad Syarif (EDUTECH, 2015)
Abstract .The purpose of this research is to analyze the relationship between students attitude to health education and learning environment by learning outcomes of health education .This   study by using methods of  survey correlation. The study is done in public primary schools in Bogor with n = 40. The sample used a technique of random sampling. The results of the study  showed: (1)  there is a positive correlation between the attitude of the student with learning out   comes health education (2) there is a positive relationship between learning environment    with learning outcomes health education  (3) there is a positive attitude of students to health   education and learning environment of the learning outcome of  health education. Based on the research showed that health education can be more optimal by raising the students attitude of education health and the environment to study for students properly.Keywords: student attitude, learning environment,  learning  outcomes  of health education.Abstrak. Tujuan dari penelitian ini adalah untuk melihat hubungan antara sikap siswa terhadap pendidikan kesehatan dan lingkungan belajar dengan hasil belajar pendidikan kesehatan. Penelitian ini menggunakan metode survey yang mengimplementasikan teknik korelasi ganda. Penelitian ini dilakukan di Sekolah Dasar  Negeri  Bogor dengan n = 40 dengan menggunakan teknik random sampling. Hasil penelitian menunjukan: (1) ada korelasi positif antara sikap siswa dengan hasil belajar pendidikan kesehatan (2) ada hubungan positif antara lingkungan belajar dengan hasil belajar pendidikan kesehatan (3) ada hubungan yang positif antara sikap siswa terhadap pendidikan kesehatan dan lingkungan belajar secara bersama-sama terhadap hasil belajar pendidikan kesehatan. Berdasarkan hasil penelitian menunjukan hasil belajar pendidikan kesehatan dapat ditingkatkan dengan meningkatkan sikap siswa terhadap pendidikan kesehatan dan lingkungan belajar siswa yang baik.Kata Kunci: Sikap siswa, lingkungan belajar, hasil belajar pendidikan kesehatan.